2018
DOI: 10.1016/j.compositesa.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of impact behavior of wood-based sandwich structures

Abstract: Low carbon emission and sustainable development are shared goals throughout the transportation industry. One way to meet such expectations is to introduce lightweight materials based on renewable sources. Sandwich panels with plywood core and fiber reinforced composite skins appear to be good candidates. Additional properties of wood such as fire resistance or thermal and acoustic insulation are also essential for many applications and could lead to a new interest for this old material. In this paper, Sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
1
33
0
2
Order By: Relevance
“…Papers [3][4][5] showed the influence of the parameters of technological processes on the mechanical characteristics of plywood, but the attention was not paid to detecting internal defects arising in the process of production and quality control of articles. The issues of flaw detection in wood and wood-based articles were tackled in [6][7][8], in which detection of internal defects involved the method of synchrotron tomography and the behavior of plywood was investigated under the action of impact influences. The method of synchrotron tomography can effectively detect internal defects, but requires the use of complex, costly, and bulky equipment, which makes it difficult to use it outside the specialized laboratories.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Papers [3][4][5] showed the influence of the parameters of technological processes on the mechanical characteristics of plywood, but the attention was not paid to detecting internal defects arising in the process of production and quality control of articles. The issues of flaw detection in wood and wood-based articles were tackled in [6][7][8], in which detection of internal defects involved the method of synchrotron tomography and the behavior of plywood was investigated under the action of impact influences. The method of synchrotron tomography can effectively detect internal defects, but requires the use of complex, costly, and bulky equipment, which makes it difficult to use it outside the specialized laboratories.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…After a first static analysis [2], the authors focused on the issue of low-velocity/low-energy impact, which is a major concern for the sizing of sandwich structures [3][4][5]. The main results of the experimental part of that study are shown in reference [6] and thus the aim of the present paper is to model impact for those particular sandwich structures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, balsa wood cores perform well under static loading, but they fail catastrophically under impact loading due to the low fracture toughness along the grain direction [28]. With regard to plywood structures, at high impact energy levels, they are perforated with heavy loss of structural integrity, which can be undesirable in most applications [29]. Previous studies also revealed that the impact damage tolerance of such wood-based materials can be increased by using them in conjunction with composite skins in sandwich designs [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to plywood structures, at high impact energy levels, they are perforated with heavy loss of structural integrity, which can be undesirable in most applications [29]. Previous studies also revealed that the impact damage tolerance of such wood-based materials can be increased by using them in conjunction with composite skins in sandwich designs [29][30][31]. Shin et al [30] showed that the energy absorption of wood-based sandwich structures was comparable with the aluminium honeycomb sandwich structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation